2017
DOI: 10.1590/2317-1782/20172015175
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre os achados do questionário de disfagia M. D. Anderson e a videofluoroscopia da deglutição após tratamento do câncer de cabeça e pescoço

Abstract: RESUMO Introdução A utilização de questionários sintoma-específicos no câncer de cabeça e pescoço (CCP) em conjunto com avaliações objetivas da deglutição pode ser sensível às mudanças na qualidade de vida (QV) decorrentes da disfagia, porém é uma ferramenta pouco utilizada como complemento de avaliações clínicas. Objetivo analisar a associação entre o questionário de disfagia M. D. Anderson (MDADI) com a videofluoroscopia (VF) da deglutição em pacientes tratados do CCP. Método Estudo retrospectivo, com rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(34 reference statements)
1
2
1
Order By: Relevance
“…Similar to previous studies, factors such as gender [6], financial burden [26], tumor stage [27], location of HNC [18], and type of treatment [13,14], this study also identified female sex, low income, suffering from hypopharyngeal cancer, and advanced tumor as the critical determinants of poor QoL related to swallowing problems among HNC patients. These results have direct implications for improving the care of HNC patients by highlighting the need to incorporate swallowing function in the assessment and clinical management of patients.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to previous studies, factors such as gender [6], financial burden [26], tumor stage [27], location of HNC [18], and type of treatment [13,14], this study also identified female sex, low income, suffering from hypopharyngeal cancer, and advanced tumor as the critical determinants of poor QoL related to swallowing problems among HNC patients. These results have direct implications for improving the care of HNC patients by highlighting the need to incorporate swallowing function in the assessment and clinical management of patients.…”
Section: Discussionsupporting
confidence: 81%
“…The composite MDADI mean scores in this study was considerably lower than 63.36 reported in Brazil [42], 64.06 and 67 and reported in USA [1,43] and 67.08 reported in Taiwan [27] indicating the severity of this problem in Ethiopia. The variation may be due to the fact that patients in Ethiopia lack access to early treatment and support since there is a single cancer center in the country that provide comprehensive cancer care.…”
Section: Discussioncontrasting
confidence: 72%
“…The MDADI has been translated and validated into Swedish and was found to have satisfactory psychometric properties 38 . A total score below 60 has been used to indicate moderate to severe dysphagia in previous studies and was therefore used as a cut‐off for severe dysphagia for patient‐reported swallowing difficulties 26,33,39‐41 …”
Section: Assessment and Endpointsmentioning
confidence: 99%
“… 38 A total score below 60 has been used to indicate moderate to severe dysphagia in previous studies and was therefore used as a cut‐off for severe dysphagia for patient‐reported swallowing difficulties. 26 , 33 , 39 , 40 , 41 …”
Section: Assessment and Endpointsmentioning
confidence: 99%